THE ROLE OF TANAMERA COFFEE BALI IN THE IMPLEMENTATION OF SUSTAINABLE TOURISM - Jati Paras Ayu; Vitha Octavanny; Ferdi Hakim (Journal of Digital Media Communication, 2023)
Sustainable tourism is a program made by the government to maintain and plan the continuation of the tourism industry. As part of the Sustainable Development Goals Agenda, sustainable tourism can improve the quality of a destination or a business. This study aims to identify the programs carried out by Tanamera Coffee Bali in implementing the concept of sustainable tourism as part of supporting the progress of tourism in Bali. This study uses qualitative research methods and descriptive analysis methods. The research results obtained are that Tanamera Coffee has implemented sustainable tourism in its business programs. It has positively impacted Tanamera Coffee, namely increasing visitors to Tanamera Coffee and giving a good reputation to the Tanamera Coffee Bali brand. The advice that can be given is Tanamera Coffee needs to periodically socialize the understanding of sustainable tourism to its employees and make it the standard for all Tanamera Coffee outlets in Indonesia and abroad.